2003
DOI: 10.1021/jf0346859
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Outcome of Blocking the Ergot Alkaloid Pathway of a Grass Endophyte

Abstract: Neotyphodium sp. Lp1, an endophytic fungus from perennial ryegrass (Lolium perenne), produces the mycotoxin ergovaline in infected grasses, whereas a mutant in which a particular peptide synthetase gene is knocked out does not. We examined the impact of this knockout on other constituents of the ergot alkaloid pathway. Two simple lysergic acid amides, ergine and a previously undescribed amide, were eliminated by the knockout. Lysergic acid accumulated in the knockout endophyte, but quantities were only 13% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
102
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(113 citation statements)
references
References 27 publications
9
102
1
1
Order By: Relevance
“…Consistent with earlier MSMS analyses demonstrating that the ergovaline pathway is fully functional within E. hybrida (Panaccione et al 2003), all genes required for ergovaline production were identified in E. hybrida Lp1 from genomic reads and appear to have been inherited as single homeologs derived from the E. festucae progenitor. (This pathway is also absent in E. typhina E8.)…”
Section: E Festucae E Typhina Nonesupporting
confidence: 84%
“…Consistent with earlier MSMS analyses demonstrating that the ergovaline pathway is fully functional within E. hybrida (Panaccione et al 2003), all genes required for ergovaline production were identified in E. hybrida Lp1 from genomic reads and appear to have been inherited as single homeologs derived from the E. festucae progenitor. (This pathway is also absent in E. typhina E8.)…”
Section: E Festucae E Typhina Nonesupporting
confidence: 84%
“…This result is not surprising since chanoclavine is an early pathway intermediate in the biosynthesis of all known ergot alkaloids and it accumulates to various degrees in different ergot alkaloid producers (7,8,14,15,25).…”
Section: Discussionmentioning
confidence: 90%
“…(15,19). However, none of the fumigaclavines produced by A. fumigatus has been detected in a member of the Clavicipitaceae.…”
mentioning
confidence: 99%
See 2 more Smart Citations